PENGARUH GCG TERHADAP FIRM VALUE DENGAN FIRM SIZE SEBAGAI VARIABEL KONTROL - Julianto, Vincentius Calvin; Sudirgo, Tony (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
The purpose of this study is to empirically prove whether there is an effect between board size, board independence, audit committee size, and CEO duality with firm size as a control variable, on firm value. The population of this study comes from infrastructure companies listed on the Indonesia Stock Exchange (IDX) in the 2016-2020 period. The sampling technique used was purposive sampling, and the total sample obtained was 80 samples. The data was processed using EViews 12 software with a multiple regression analysis method. The results of the analysis of this study found that board size has a significant effect on firm value, while board independence, audit committee size, CEO duality, and firm size as control variables do not have a significant effect on firm value. The implication of this research is the need to use more specific GCG in financial statements in order to provide added value for investors.